Blue Economy Concept in Extension Waste of Fish Baung Into Fish Oil in Sungai Paku Village Kampar Kiri, Kampar Regency, Riau Province - Mirna Ilza; Ikhsan Ikhsan; Azhari Azhari; Buchori Buchori (Universitas Riau, 2020)
Service to the public entitled